Unlocking C–OH Bond Activation for Radical C-Glycosylation of Native Saccharides - Wang, Sheng; Guo, Peng; Shu, Xing-Zhong (Synlett, 2025)
Due to their enhanced metabolic stability, C-glycosides are valuable structural motifs in bioactive natural products and pharmaceuticals. However, direct C-glycosylation of native saccharides remains a significant challenge due to the inert nature of the C–OH bond and the inherent selectivity issues arising from multiple hydroxy groups. In this Synpacts article, we highlight our recent development of a titanium-catalyzed radical C-glycosylation strategy that enables selective C–OH bond activation without prefunctionalization. By leveraging a Cp*TiCl₃/Zn system, this method generates glycosyl radicals under mild conditions, facilitating stereoselective C-glycosylation with electron-deficient alkenes. The approach exhibits a broad substrate scope that includes monosaccharides, disaccharides, and complex bioactive molecules, offering significant potential utility in glycodrug discovery. Radical stabilization and stereoelectronic effects drive the observed axial selectivity (>20:1). This work establishes a powerful and practical platform for C-glycoside synthesis, addressing long-standing challenges in carbohydrate functionalization and opening new avenues for radical-mediated glycosylation strategies.
Keywords: glycosylation; glycosides; titanium catalysis; radical reaction; Giese reaction